Analisis Kesulitan Guru Bersertifikasi Dalam Penulisan Karya Ilmiah(Studi Kasus pada Guru-Guru Bersertifikasi di SMK Sakti Gemolong) - Nur Syakbaniyah, Siti, Prof. Bambang Sumardjoko (2017)
This research aims to mendiskripsikan: (1) an understanding of writing scientific papers on certified teachers educators in SMK Sakti Gemolong. (2) the attitude/responses on writing scientific papers certified teachers educators in SMK Sakti Gemolong. (3) the difficulty in writing scientific papers certified teachers educators in SMK Sakti Gemolong. (4) the effort of overcoming the difficulties in writing scientific papers for certified teachers educators in SMK Sakti Gemolong. This research is qualitative research with ethnographic methods. The methods used in data collection is interviews, observation and documentation. Testing the validity of the data using the triangulation of the data. Data analysis techniques include: collection, data presentation, data reduction, and withdrawal of the conclusion or evaluation. Conclusions in this study are: (1) there are still many teachers who do not yet know about the writing of scientific papers. (2) the activities recommended to Attempt the creation of a scientific paper for teachers certified in SMK Milky still not optimally. (3) the problems or obstacles faced by teachers certification in the form of lack of awareness of the importance of writing scientific papers, lack of knowledge about the writing of scientific papers and a lack of commitment. (4) the effort that's been done is formed the team supervising the writing of scientific works, formed the Forum of scientific Paper Studies teacher in SMK Milky Gemolong